Mastering Linux Shell Scripting : a practical guide to Linux command-line, Bash scripting, and Shell programming, 2nd Edition. - Ebrahim, Mokhtar (Packt Publishing, 2018)
Shell scripting is a quick method to prototype a complex application or a problem by automating tasks when working on Linux-based systems. This book will make use of both simple one-line commands and command sequences and complex problems can be solved with ease, from text processing to backing up sysadmin tools.